PENGALAMAN SANTRI MENGIKUTI PROGAM GPM (GERAKAN PONDOK MENYENANGKAN) TERHADAP PERILAKU BULLYING DI PESANTREN - Retnowuni, Arifa; Linda Yani, Athi? (Jurnal EDUNursing, 2019)
ABSTRACT Dormitory is a place for both formal and non-formal education. Santri follows all activities in dormitory and almost spends all of his time to following all rules and regulations in dormitory. Santri may not leave the dormitory without permission from the supervisor and may not carry communication devices or electronics, students who came have different cultural backgrounds and the intensity of time to meet among roommates longer so that the risk for acts of bullying behavior is higher among peers. The purpose of this study is to explore the experience of students during the GPM program in dipesantren. The research method uses descriptive qualitative phenomenology, with the determination of participants using purposive sampling, participants are students who take the GPM program totaling 5 respondents. Data collection techniques with in-depth interviews after that the data were analyzed to determine the sub themes and themes, the results of this study resulted in four themes namely (1) mutual respect, (2) providing assistance, (3) increasing motivation, (4) feeling happy. This research can increase students' self-awareness and understanding of bullying behavior which should not be carried out continuously. Santri feels happy and there is no sense of worry or fear when together with friends.Keywords ; experience, GPM program, students